2015
DOI: 10.1007/s00296-015-3366-2
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab as a treatment option for patients with rheumatoid arthritis and primary biliary cirrhosis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory systemic disease which commonly requires treatment with biologic agents targeting various inflammatory pathways. Tumor necrosis factor alpha is a proinflammatory cytokine which plays a pivotal role not only in the pathogenesis of RA but also in other autoimmune diseases such as primary biliary cirrhosis. The co-existence of more than one autoimmune disorder in the same individual is very challenging in the daily practice as therapy strategies applicable to on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…PBC is considered an immunologically mediated disease where the TNF-α plays a prominent pathogenic role [10]. The unique data published on the use of IFX in PBC are collected in patients with RA and PBC.…”
Section: Potential Beneficial Effects Of Anti-tnf-α On Liver Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…PBC is considered an immunologically mediated disease where the TNF-α plays a prominent pathogenic role [10]. The unique data published on the use of IFX in PBC are collected in patients with RA and PBC.…”
Section: Potential Beneficial Effects Of Anti-tnf-α On Liver Diseasesmentioning
confidence: 99%
“…While TNF-α inhibitors are a well-established treatment option for RA, the experience of using such regimens when inflammatory arthritis coexists with PBC is inconclusive. Garyfallos et al [10] reported a case of a female patient with RA and concomitant PBC with poor clinical response to conventional treatment. IFX use led to a significant clinical improvement of RA and to the stabilization of liver function.…”
Section: Potential Beneficial Effects Of Anti-tnf-α On Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…tiene la particularidad de mostrar que los parámetros de CBP que habían mejorado con etanercept, empeoraron al suspenderlo y volvieron a mejorar al reintroducirlo 10 . otra paciente recibió infliximab y tras 24 meses las enzimas hepáticas permanecieron estables y normales 11 . Existe solo un caso reportado en Croacia (publicación sin referato) con adalimumab en el cual ambas enfermedades se mantuvieron en una larga remisión.…”
Section: Discussionunclassified
“…IFX targets one of the pathogenic proinflammatory cytokines, tumor necrosis factor-alpha (TNF-α), and thus has been applied in classical TNF antagonist therapy against multiple chronic autoimmune inflammatory diseases, including RA [23]. The clinical application of IFX has been studied for nearly 30 years; IFX greatly improves physical functions and is beneficial for the achievement of clinical remission even under discontinuous medication [24,25]. However, not all patients react to IFX, and its anti-inflammatory effects vary among patients with RA.…”
Section: Introductionmentioning
confidence: 99%